Answer:
B. -1
Step-by-step explanation:
If we have a parabola whose equation is:
![y=ax^{2} +bx+c](https://tex.z-dn.net/?f=y%3Dax%5E%7B2%7D%20%2Bbx%2Bc)
The line of symmetry is calculated as:
![x=\frac{-b}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%7D%7B2a%7D)
Now, we have the equation
and the line of symmetry is ![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Where:
![b=-4\\c=3](https://tex.z-dn.net/?f=b%3D-4%5C%5Cc%3D3)
So, we can replace
by -4 and
by -2 and solve for
using the following equation as:
![x=\frac{-b}{2a}\\-2=\frac{-(-4)}{2a}\\-2(2)a=4\\-4a=4\\a=-1](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%7D%7B2a%7D%5C%5C-2%3D%5Cfrac%7B-%28-4%29%7D%7B2a%7D%5C%5C-2%282%29a%3D4%5C%5C-4a%3D4%5C%5Ca%3D-1)
It means that the equation of the parabola is equal to:
![y=-1x^{2}-4x+3](https://tex.z-dn.net/?f=y%3D-1x%5E%7B2%7D-4x%2B3)
M equals c over e is not equal to e=mc
Answer:
25.44$
Step-by-step explanation:
20% of $30 = 6 $
Cost = 24$
Tax = 1.44$
Total cost = 25.44$
HOPE THIS HELPS
PLZZ MARK BRAINLIEST
Answer: Aproxamatly 18.999999999999999
Step-by-step explanation: